A pilot evaluation of whole blood finger-prick sampling for point-of-care HIV viral load measurement: the UNICORN study. Issue 1 (December 2017) - Fidler, Sarah; Lewis, Heather; Meyerowitz, Jodi; Kuldanek, Kristin; Thornhill, John; Muir, David; Bonnissent, Alice; Timson, Georgina; Frater, John
Abstract There is a global need for HIV viral load point-of-care (PoC) assays to monitor patients receiving antiretroviral therapy. UNICORN was the first study of an off-label protocol using whole blood finger-prick samples tested with and without a simple three minute spin using a clinic-room microcentrifuge. Two PoC assays were evaluated in 40 HIV-positive participants, 20 with detectable and 20 with undetectable plasma viral load (pVL) (<20 copies/ml). Using 100 µl finger-prick blood samples, the Cepheid Xpert HIV-1 Viral Load and HIV-1 Qual cartridges were compared with laboratory pVL assessment (TaqMan, Roche). For participants with undetectable viraemia by TaqMan, there was poor concordance without centrifugation with the TaqMan platform with only 40% 'undetectable' using Xpert VL and 25% 'not detected' using the Qual assay. After a 3 minute spin, 100% of samples were undetectable using either assay, showing full concordance with the TaqMan assay. Defining a lower limit of detection of 1000 copies/ml when including a spin, there was 100% concordance with the TaqMan platform with strong correlation (rho 0.95 and 0.94; p < 0.0001 for both assays). When including a simple microcentrifugation step, finger-prick PoC testing was a quick and accurate approach for assessing HIV viraemia, with excellent concordance with validated laboratory approaches.